2003
DOI: 10.1097/00019052-200312000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Upper and lower extremity robotic devices for rehabilitation and for studying motor control

Abstract: Technical possibilities are one aspect, but multi-centre trials and a consideration of the unsubstantiated fears among therapists of being replaced by machines will decide on the successful implementation of this most promising field to the benefit of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
168
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(173 citation statements)
references
References 14 publications
3
168
0
2
Order By: Relevance
“…Small trials have shown modest clinical improvement in disabilities after stroke with the use of the following techniques: electrical stimulation over the surface of muscles to contract them for simple movements, such as grasping, or to assist ankle dorsiflexion while walking 49 ; intense practice with electromechanical devices that assist in reaching or stepping 50 ; noninvasive stimulation of the peripheral nerve of the arm 51 or direct stimulation of the motor cortex over the hand representation 52 to augment cortical plasticity and learning during arm therapies; pharmacotherapy with agonists of dopamine, acetylcholine, and serotonin, which may modulate neurotransmission and learning 53 ; and the use of mental imagery of an action, 54 which may enhance training because it activates many of the same cortical neurons that are involved in performing the action. Phase 1 trials are beginning in order to assess the safety of the injection of drugs into the cerebrospinal fluid or of cells into brain tissue to replace neurons and promote dendrite sprouting and axon regeneration, 55 with the goal of possible neural repair.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…Small trials have shown modest clinical improvement in disabilities after stroke with the use of the following techniques: electrical stimulation over the surface of muscles to contract them for simple movements, such as grasping, or to assist ankle dorsiflexion while walking 49 ; intense practice with electromechanical devices that assist in reaching or stepping 50 ; noninvasive stimulation of the peripheral nerve of the arm 51 or direct stimulation of the motor cortex over the hand representation 52 to augment cortical plasticity and learning during arm therapies; pharmacotherapy with agonists of dopamine, acetylcholine, and serotonin, which may modulate neurotransmission and learning 53 ; and the use of mental imagery of an action, 54 which may enhance training because it activates many of the same cortical neurons that are involved in performing the action. Phase 1 trials are beginning in order to assess the safety of the injection of drugs into the cerebrospinal fluid or of cells into brain tissue to replace neurons and promote dendrite sprouting and axon regeneration, 55 with the goal of possible neural repair.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…Two current examples include robotic treadmill ambulation devices and robotic upper limb-retraining devices. 15 Research has found that repetitive movement can enhance the return of motor function. These exoskeletally applied rehabilitative robotics are ideally suited to this role and have the added benefit of measurable outcomes, a critical issue in healthcare.…”
Section: Impact On Specific Devices Roboticsmentioning
confidence: 99%
“…The feedback can be provided either after a task in the form of scores, or during the task using dynamic biofeedback visual and auditory cues [16]. Some systems also provide physical assistance with movement and/or simulate haptic feedback [7,13,17,18,20,21,26,34].…”
Section: Introductionmentioning
confidence: 99%